Effectiveness of Responsibility Training Based on Choice Theory on School Belonging and Quality of Teacher-Student Relationship in Female Students - Mohammad Geravandnia; Esmail Sadipour; Hasan Asadzadeh; Soghra Ebrahimi Ghavam (Iranian Journal of Educational Research)
Objective: The objective of this study was to examine the effectiveness of responsibility education, based on choice theory, on the school belonging and the quality of student-teacher relationships in female high school students. Methods: The research design employed an applied objective approach and utilized a quasi-experimental design (pre-test-post-test with control group). The study population consisted of second-year high school students in the 2nd district of Karaj city, enrolled during the academic year of 2022-2023. Among them, a sample of 30 individuals was selected using the available sampling method and divided into two groups: the experimental group (15 students) and the control group (15 students). The data collection instruments included the Brew et al. questionnaire on students' sense of connectedness with school (2004) and Newman's quality of learning experience questionnaire (1990). The collected data was analyzed using SPSS version 26 software and multivariate covariance analysis. Results: The findings revealed a significant difference between the experimental and control groups in terms of the development of school belonging and the quality of student-teacher relationships among high school students. Specifically, responsibility education based on choice theory was found to enhance the school belonging and improve the quality of student-teacher relationships. Conclusions: The provision of training and the cultivation of students' sense of responsibility not only strengthens their connection with the school but also enhances the quality of their relationships with teachers.